(3fKjQ aQGFO GdLeGf aj fXe aMhd GdReGfs - (3GHf GdCMeQ , ESeGYjd Hf jhSa Hf eMeO Hf fUQ GdNRQLj GdfUQj, CHh GdhdjO,J (B807 (3g` s
(3ChdgG (B:s
(3hHYO, aEf GdCOH RgQ MhJg ef GdHOGFY ceGeg, hQhV eOjM MGcJg ef GdeMGeO ZeGeI s
(3BNQgG (B:s
(3hJhQOJ ef EUGHJg MOhOg aUQag edRe GdbhGaj, Jcf aj GdCOH eRjO GdNhGaj s
(3HgG fXGe GdJYbjHIs
(3aj Cgd GdeFI GdKGefIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B329s
(3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B1 - (3bSe (B6 - (3U (B132 s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdCOHs